BIIB093 (IV glibenclamide): an investigational compound for the prevention and treatment of severe cerebral edema. (2nd December 2019) - Pergakis, Melissa; Badjatia, Neeraj; Chaturvedi, Seemant; Cronin, Carolyn A.; Kimberly, W. Taylor; Sheth, Kevin N.; Simard, J. Marc
ABSTRACT: Introduction : Brain swelling due to edema formation is a major cause of neurological deterioration and death in patients with large hemispheric infarction (LHI) and severe traumatic brain injury (TBI), especially contusion-TBI. Preclinical studies have shown that SUR1-TRPM4 channels play a critical role in edema formation and brain swelling in LHI and TBI. Glibenclamide, a sulfonylurea drug and potent inhibitor of SUR1-TRPM4, was reformulated for intravenous injection, known as BIIB093. Areas covered : We discuss the findings from Phase 2 clinical trials of BIIB093 in patients with LHI (GAMES-Pilot and GAMES-RP) and from a small Phase 2 clinical trial in patients with TBI. For the GAMES trials, we review data on objective biological variables, adjudicated edema-related endpoints, functional outcomes, and mortality which, despite missing the primary endpoint, supported the initiation of a Phase 3 trial in LHI (CHARM). For the TBI trial, we review data on MRI measures of edema and the initiation of a Phase 2 trial in contusion-TBI (ASTRAL). Expert opinion : Emerging clinical data show that BIIB093 has the potential to transform our management of patients with LHI, contusion-TBI and other conditions in which swelling leads to neurological deterioration and death.